Are medical students being taught anatomy in a way that best prepares them to be a physician?. Issue 5 (14th May 2015) - Meral Savran, Mona; Tranum‐Jensen, Jørgen; Frost Clementsen, Paul; Hastrup Svendsen, Jesper; Holst Pedersen, Jesper; Seier Poulsen, Steen; Arendrup, Henrik; Konge, Lars
<x xml:space="preserve">Abstract</x> Reasoning in a clinical context is an attribute of medical expertise. Clinical reasoning in medical school can be encouraged by teaching basic science with a clinical emphasis. The aim of this study was to investigate whether anatomy is being taught in a way that facilitates the development of clinical reasoning. Two multiple‐choice tests on thoracic anatomy were developed using a modified Delphi approach with groups of four clinical consultants and four teachers, respectively, expressing their opinions about knowledge relevant to thoracic anatomy. Validity was assessed by administering the tests to clinical consultants, anatomy teachers, and pre‐course medical students. Post‐course medical students took both tests to explore the focus of the course, i.e., whether it facilitated clinical reasoning. The pre‐course students scored significantly lower than the teachers and post‐course students on both tests and lower than the consultants on the consultants' test (P < 0.001 for all comparisons). The teachers significantly outperformed the consultants (P = 0.03 on the consultants' test, P < 0.001 on the teachers' test) and the medical students (P < 0.001 on both tests). The post‐course students scored significantly lower on the consultants' test (P = 0.001) and significantly higher on the teachers' test (P = 0.02) than the consultants. This study demonstrates poor performances by medical students on a test containing clinically relevant anatomy, implying that the teaching they have received has not encouraged clinical reasoning. Clin. Anat. 28:568–575, 2015. © 2015 Wiley Periodicals, Inc.